2018
DOI: 10.1088/1361-6595/aacdb0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of discharge triggering in micro-cathode vacuum arc thruster for CubeSats

Abstract: The ignition and optimization of the pulsed micro-cathode triggerless vacuum arc thruster model are analyzed. To this end a simplified model of the thruster consisting of two rectangular electrodes on an alumina ceramic plate with a variable inter-electrode gap covered by a conductive film of carbon paint is considered. It is shown that after optimizing the inter-electrode gap, the electrical power and the value of the magnetic field parallel to the film surface, such an 'idealized' thruster model can provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…Low-power vacuum arc thrusters have the known problem of a limited lifetime, which may vary from 10 3 ( 26 ) to 10 5 pulses ( 27 ), while the special constructions with the cathode feeding mechanism allow the achievement of several million pulses ( 28 ). In our previous study ( 29 ), we found that the lifetime of the μCAT firing in the high-power regime can be extended to more than 1 million pulses by optimizing the anode-cathode gap (extending it to around 1 mm) and providing the magnetic field, causing the movement of cathodic spot along the cathode surface. Thus, the configuration of the first-stage electrodes of the newly designed μCAT-MPD thruster was chosen to provide the maximal lifetime even at a high-power performance.…”
Section: Discussionmentioning
confidence: 99%
“…Low-power vacuum arc thrusters have the known problem of a limited lifetime, which may vary from 10 3 ( 26 ) to 10 5 pulses ( 27 ), while the special constructions with the cathode feeding mechanism allow the achievement of several million pulses ( 28 ). In our previous study ( 29 ), we found that the lifetime of the μCAT firing in the high-power regime can be extended to more than 1 million pulses by optimizing the anode-cathode gap (extending it to around 1 mm) and providing the magnetic field, causing the movement of cathodic spot along the cathode surface. Thus, the configuration of the first-stage electrodes of the newly designed μCAT-MPD thruster was chosen to provide the maximal lifetime even at a high-power performance.…”
Section: Discussionmentioning
confidence: 99%
“…Water cooling of the cathode units of both the magnetron and the vacuum arc is supplied through insulating water decoupling with a channel length of 5 m and diameter 3 mm. The discharge plasma of a magnetron discharge, supported by the plasma of a vacuum arc, fills the expander (9), which is electrically connected to anodes 2 and 6 unless otherwise specified. The expander metal grid with mesh size of 0.7 mm × 0.7 mm forms the plasma emission surface.…”
Section: Methodsmentioning
confidence: 99%
“…The use of such a plasma in an ion source will ensure the formation of metal ion beams. The demand for metal ions is associated with their use in accelerator technology [8], ion thrusters [9], as well as in technological installations of ion implantation for hardening the surface properties of various materials [10]. At present, ion sources based on a vacuum arc with a cathode spot are mainly used to generate beams of metal ions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Постійний інтерес вчених до плазмових технологій ґрунтується на досить широких можливостях їх використання, наприклад для осадження тонких металевих плівок [1,2], генерації лазерної плазми [3,4] або як джерело енергії для космічних плазмових двигунів [5,6]. Численні дослідження процесів, які відбуваються у плазмовому середовищі [7,8], та їх параметрів [9,10] дають нові можливості для удосконалення технологій та їх використання.…”
Section: вступunclassified